2016
DOI: 10.1186/s12955-016-0479-6
|View full text |Cite
|
Sign up to set email alerts
|

Child maltreatment and quality of life: a study of adolescents in residential care

Abstract: BackgroundChildhood maltreatment is an important risk factor for mental and physical health problems. Adolescents living in residential youth care (RYC) have experienced a high rate of childhood maltreatment and are a high-risk group for psychiatric disorders. Quality of life (QoL) is a subjective, multidimensional concept that goes beyond medical diagnoses. There is a lack of research regarding the associations between childhood maltreatment and QoL. In the present study, we compare self-reported QoL between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 58 publications
1
37
1
2
Order By: Relevance
“…Even when the same specific self-esteem domain is evaluated as important for QoL in different populations, the reasons for this could be different. A large portion of the adolescents had experienced sexual abuse as we have shown in previous reports on this sample [28,54]. Patients with a history of child sexual abuse and post-traumatic stress disorder report aversive emotional responses, negative cognitions, and dissociative states triggered by viewing their own body in a mirror [55].…”
Section: Physical Appearance and Qolmentioning
confidence: 59%
“…Even when the same specific self-esteem domain is evaluated as important for QoL in different populations, the reasons for this could be different. A large portion of the adolescents had experienced sexual abuse as we have shown in previous reports on this sample [28,54]. Patients with a history of child sexual abuse and post-traumatic stress disorder report aversive emotional responses, negative cognitions, and dissociative states triggered by viewing their own body in a mirror [55].…”
Section: Physical Appearance and Qolmentioning
confidence: 59%
“…In two previous studies on the same study population of adolescents in RYC, an association between experienced childhood maltreatment (witnessing violence, victim of family violence, victim of sexual abuse, household dysfunction) and both a broad spectrum of psychiatric disorders and a poor QoL was found (Greger et al, , 2016. In this study we want to explore underlying mechanisms by studying global self-esteem, attachment difficulties and substance use as possible mediating factors of the associations between childhood maltreatment and psychopathology, and between childhood maltreatment and well-being.…”
Section: Introductionmentioning
confidence: 79%
“…Regarding the subjective experience of quality of life (QoL), as measured by KINDL‐R (Ravens‐Sieberer & Bullinger, ), our results showed that adolescents in RYC report lower subjective quality of life in the areas of physical and emotional well‐being, self‐esteem and relationship with friends compared with young people in the general population (Jozefiak & Kayed, ). In addition, poor QoL was associated with experienced childhood maltreatment (Greger, Myhre, Lydersen, & Jozefiak, ). The adolescents' self‐esteem domains − social acceptance and physical appearance − added substantially to the explained variance in QoL among adolescents living in RYC, over and beyond the levels of psychopathology (Jozefiak et al, ).…”
Section: Norwegian Knowledge Base On Mental Health Of Children In Altmentioning
confidence: 99%
“…Further research is needed to gain more knowledge about how to best combine screening instruments to adequately capture dimensions of psychopathology that are especially relevant for this high‐risk group of children. Although the early identification and assessment of healthcare needs is of major importance for these children and adolescents, more emphasis should also be given to systematic identification of maltreatment, as this is associated with mental disorders (Gover, ; Greger et al, ; Kaplan et al, ; Lehmann et al, ; McLaughlin et al, ; Mills et al, ), poor QoL (Greger et al, ) and poor physical health in a long‐term perspective (Rich‐Edwards et al, ; Springer, Sheridan, Kuo, & Carnes, ; Thurston et al, ). There are several standardised instruments available for assessing maltreatment history and trauma‐related symptoms, for example the Childhood Trauma Questionnaire (Bernstein & Fink, ; Bernstein et al, ), validated in Nordic samples.…”
Section: Recommendation For Clinical Practice; Tools For Early Identimentioning
confidence: 99%